Questioning the Legal Considerations of Interfaith Marriage from the Perspective of Islamic Law and Positive Law in Indonesia - Najib, Muhammad; Marilang, Marilang; Talli, Abdul Halim (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
The purpose of this study is to analyze the legal considerations of interfaith marriage in Indonesia in the perspective of Islamic law and positive law in Indonesia. The author uses a normative juridical approach. This research is classified as library research, the data collected is analyzed usingcontent analysis of representative literature and has relevance to the issues discussed, then compared usingcomparative analysis, then reviewed, and concluded. The results show that interfaith marriage has no legal basis in either Islamic law or the Marriage Law. The consideration of the legalization of interfaith marriage in the form of the applicant's human rights to the claim of a legal vacuum is an erroneous legal consideration. Allowing interfaith marriages in Indonesia tends to potentially cause various problems. Therefore, the prohibition of interfaith marriage is more in line with the reality and needs in Indonesia. The study of interfaith marriage needs to receive more attention because the law can change according to changes in time and place. In addition, the prohibition of interfaith marriage needs to be socialized to the public in a simple and easy-to-understand language because the negative impact of different opinions on interfaith marriage often arises in the midst of ordinary people.